2008
DOI: 10.1007/s12098-008-0002-0
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial bloodstream infection in a pediatric intensive care unit

Abstract: The predominant organisms responsible for nosocomial infection in the PICU were Klebsiella pneumoniae , Staphylococcus aureus and Enterobacter species . At present, carbapenems plus vancomycin appear to be the best choice for empiric antibiotic therapy in the PICU in Chandigarh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 12 publications
3
18
1
1
Order By: Relevance
“…Some of possible factors for this may be malnourished state of patients, delayed presentation to referral centers and multi-organ involvement at admission. 21 The prevalence of nosocomial infections n ICU in our study is higher than the study of Dusgupta et al 22 19 in neonatal ICU coagulase-negative staphylococci is common isolate in blood culture. Gram-negative bacteria, especially Klebsiella spp., were the predominant causes of neonatal NI, as has been described in other studies from developing countries.…”
Section: Discussioncontrasting
confidence: 63%
“…Some of possible factors for this may be malnourished state of patients, delayed presentation to referral centers and multi-organ involvement at admission. 21 The prevalence of nosocomial infections n ICU in our study is higher than the study of Dusgupta et al 22 19 in neonatal ICU coagulase-negative staphylococci is common isolate in blood culture. Gram-negative bacteria, especially Klebsiella spp., were the predominant causes of neonatal NI, as has been described in other studies from developing countries.…”
Section: Discussioncontrasting
confidence: 63%
“…Onethird to one-half of all of the S. aureus isolates was noted to be MRSA over the duration of the study. In light of these findings, the authors' choice for empiric antimicrobial coverage was vancomycin and carbapenem [6].…”
Section: Catheter-related Blood Stream Infectionsmentioning
confidence: 99%
“…Although serious infection may prompt admission to the PICU, infection may also be a complication after admission has occurred [2]. Multiple sources have documented that the incidence of nosocomial infections due to antibiotic-resistant organisms is increasing, with specific examples in the Pediatric Intensive Care Unit (PICU) [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…But on the other hand, a study of 841 patients done in tertiary care teaching hospital showed that klebisiella pneumonia was predominant (12).…”
Section: Discussion:-mentioning
confidence: 99%
“…Studies had shown that nosocomial infection is strongly associated with prolonged hospital stay and increase the economic burden on the health care system (2). Many studies had shown that the most common organisms are gram-negative bacteria as Klebsiella pneumonia, E-coli, and pseudomonas aeruginosa, followed by gram positive bacteria as staphylococcus aureus, and enterococci (3). The most common type of infections are blood stream infection, followed by pneumonia, and UTI (4).…”
Section: Introduction:-mentioning
confidence: 99%